Effects of Multipath and Conventional NMES on Maximum Comfortable Stimulus and Torque Production - Cody B. Bremner; William R. Holcomb (Central European Journal of Sport Sciences and Medicine, 2019)
A novel multipath NMES (m-NMES) device has shown improved outcomes relative to conventional NMES (c-NMES) during recent basic and training studies. However, the mechanisms by which m-NMES outperformed c-NMES remain unclear. This study aimed to better understand these mechanisms by comparing the effects of m-NMES and c-NMES on maximum comfortable stimulus intensity and the subsequent NMES-induced torque, as these variables ultimately impact NMES training intensity; which is considered to be the primary determinant of NMES effectiveness. We measured maximum comfortable stimulus intensity and the subsequent NMES-induced torque while participants performed NMES-induced contractions under two conditions (m-NMES and c-NMES). Maximum comfortable stimulus intensity was significantly greater under the m-NMES condition, but the subsequent NMES-induced torque was not significantly different across conditions. m-NMES does not appear to influence the outcomes in a clinically meaningful manner, since it performed similarly to c-NMES with respect to peak NMES-induced torque.